An Extremal Problem on Non-overlapping Domains Containing Ellipse Points - Zabolotnii, Yaroslav; Denega, Iryna (Eurasian Mathematical Journal, 2021)
An extremal problem of geometric function theory of a complex variable for the maximum of products of the inner radii on a system of n mutually non-overlapping multiply connected domains Bk containing the points ak, k = 1, n, located on an arbitrary ellipse x²/d² + y²/t² = 1 for which d²−t² = 1, is solved.